ANALISIS CAMEL DALAM MENILAI TINGKAT KESEHATAN BPR PERIODE 2021-2023 - Dewi, Mariana Puspa (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This study aims to determine the level of health of BPR Delta Sari Kencana using CAMEL method over the period 2021-2023 are included in the category of healthy, less CAMEL has five aspects, namely capital using the ratio of CAR (Capital Adequacy Ratio) , aspects of asset quality using the ratio KAP (Assets Quality) and PPAP (Allowance for Earning Assets), management uses calculations general management and risk management , aspects of profitability using ROA (Return On Assets) and ROA (Operating Expenses to Operating Income), and use the liquidity aspect ratio of Cash Ratio and LDR (Loan to Deposit Ratio). This research is quantitative . The analytical tool used in this research is by using the CAMEL based on the Decree of Directors of Bank Indonesia Number 30/12 / KEP / DIR dated 30 April 1997 concerning Procedures for Evaluation of Health RB . As a benchmark for determining the soundness of a bank after conducting an assessment of each variable, by determining the results of the study were classified into health predicate BPR . The type of data used is primary data obtained through interviews and secondary data, the financial statements of the balance sheet and income statement Delta Sari Kencana years 2022-2023. Based on the results of the research that has been done on BPR Delta Sari Kencana stated that the level of health BPR Delta Sari Kencana period of 2021 to 2023 received the title healthy because CAMEL credit score of more than 81 (the minimum limit of healthy ) is 99.71 in 2021, 98.2 in 2022 and 98,2 in 2023. Keywords: CAMEL Methods, Health Level, Management